Presence of the tet(O) Gene in Erythromycin- and Tetracycline-Resistant Strains of Streptococcus pyogenes and Linkage with either the mef(A) or the erm(A) Gene - Giovanetti, Eleonora (American Society for Microbiology, 2003)
Sixty-three recent Italian clinical isolates of Streptococcus pyogenes resistant to both erythromycin (MICs ≥ 1 μg/ml) and tetracycline (MICs ≥ 8 μg/ml) were genotyped for macrolide and tetracycline resistance genes. We found 19 isolates carrying the mef(A) and the tet(O) genes; 25 isolates carrying the erm(A) and tet(O) genes; and 2 isolates carrying the erm(A), tet(M), and tet(O) genes. The resistance of all erm(A)-containing isolates was inducible, but the isolates could be divided into two groups on the basis of erythromycin MICs of either >128 or 1 to 4 μg/ml. The remaining 17 isolates included 15 isolates carrying the erm(B) gene and 2 isolates carrying both the erm(B) and the mef(A) genes, with all 17 carrying the tet(M) gene. Of these, 12 carried Tn916-Tn1545-like conjugative transposons. Conjugal transfer experiments demonstrated that the tet(O) gene moved with and without the erm(A) gene and with the mef(A) gene. These studies, together with the results of pulsed-field gel electrophoresis experiments and hybridization assays with DNA probes specific for the tet(O), erm(A), and mef(A) genes, suggested a linkage of tet(O) with either erm(A) or mef(A) in erythromycin- and tetracycline-resistant S. pyogenes isolates. By amplification and sequencing experiments, we detected the tet(O) gene ca. 5.5 kb upstream from the mef(A) gene. This is the first report demonstrating the presence of the tet(O) gene in S. pyogenes and showing that it may be linked with another gene and can be moved by conjugation from one chromosome to another.